Distributed operating systems - Pradeep R. Sinha (Iee Press, 1997)
Fundamentals; Computer networks; Message passing; Remote procedure calls; Distributed shared memory; Synchronization; Resource management; Process management; Distributed file systems; Naming; Security; Case studies.